REINTERPRETASI HADIS PERINTAH “MEMBUNUH MANUSIA SAMPAI MENGUCAP SYAHADAT” SEBAGAI UPAYA DERADIKALISASI AGAMA - Muhammad Mundzir (UIN Sayyid Ali Rahmatullah Tulungagung, 2019)
Starting from radicalism in Indonesia in the name of Islam, this paper tries to describe how the hadith is understood about